Sustainable Artisanal Livelihoods and Ecology of Wood Resource Use: The Case of Traditional Toy-Making in Channapatna, South India - Bhaskar, Dhanya; Ramananda, Samudyatha (Indian Forester, 2023)
Rural artisanal livelihoods are inextricably linked to local resources and for wood carvers, easy availability of wood resources is a crucial determinant of livelihood security. Our study is focused on the sustainability of the key raw material, Wrightia tinctoria L. (ivory tree), for the famous wooden toy-making industry in Channapatna, Karnataka, South India. Our research investigated the trends in use of ivory wood and the status of Wrightia trees in farmlands. Group interactions and semi-structured interviews were conducted in seven artisanal clusters in Channapatna to elucidate livelihood implications of toy-making industry and trends in wood resource use and supply. Further, tree-growing farmers and wood traders were interviewed to trace the wood supply chain. The research highlights the critical role of ivory wood in supporting livelihoods of marginalised sections of artisans and reveals the immense pressure on local ivory wood resources. The study puts forth recommendations to ensure sustained availability of the resource.